Identification Protocol of Yoshida-Uemori Hardening Model. Issue 1 (1st May 2022) - Lemoine, X; Chichery, Q; Devin, J M; Duroux, P
Abstract: The Yoshida-Uemori model is a combined hardening model coupled with the elastic modulus evolution which depends on the equivalent plastic strain. A lot of publications show that it allows to improve the springback prediction compared to a classical isotropic hardening model. It is implemented in the most used FEA stamping codes (Autoform®, Ls-Dyna® and Pamstamp®) with some variations and it is more and more used in automotive industry. ArcelorMittal decided to provide material cards to its customers. To achieve this goal, ArcelorMittal has at one's disposal the equipment to perform reverse shear tests and hysteresis loops for all steel grades. An in-house methodology has been developed to identify the Yoshida-Uemori adjusting parameters in a very precise and robust manner. The material cards are produced for each FEA stamping code, considering the specificities of the implementations.